The Phenomenon of Security: Socio-Philosophical Context - Olga V. Dzhavad; Marina L. Ivleva (RUDN Journal of Philosophy, 2025)
This research delves into the socio-philosophical dimensions of security, assessing its metaphysical and existential aspects and considering how existential threats reshape philosophical perspectives in the contemporary society. The relevance of this study is underscored by the urgent need to understand how traditional and non-traditional security threats - ranging from military conflicts to cybercrime and climate change - impact societal structures and individual freedoms. The paper highlights the intersection of social structures and security, revealing how security is instrumentalised by various actors, including governments, to control or influence social dynamics. Moreover, it emphasizes how media representation and public fear can influence political decision-making, urging a critical examination of how security discourses are constructed and whose interests they serve. By integrating socio-philosophical perspectives, this paper establishes a framework for understanding security as a multifaceted phenomenon. Notably, this research underscores the role of cultural, psychological, and ethical dimensions in shaping public understanding and policy responses to security threats. Key findings illustrate that contemporary security cannot be narrowly defined; rather, it necessitates an integrated approach encompassing political, economic, social, and environmental considerations and a re-evaluation of traditional security models to address contemporary challenges such as cybersecurity threats and digital ethics. Ultimately, this work argues for highlighting the necessity of interdisciplinary approaches in developing contemporary security strategies effectively addressing fluctuating dynamics of the international agenda.